Impacts of center pivot irrigation system uniformity on growth of potato crop and residual soil nitrogen - Al-Gaadi, Khalid A.; Hassaballa, Abdalhaleem A.; Tola, ElKamil; Kayad, Ahmed G.; Madugundu, Rangaswamy; Assiri, Fahad; Edrris, Mohamed; Alameen, Ahmed; Edrees, Haroon (International Journal of Agricultural and Biological Engineering, 2019)
Maintaining the homogeneity of soil nitrogen (N) and plant vigor across agricultural fields is a major concern for farmers and agricultural scheme planners, particularly fields that are irrigated through pressurized systems, such as center pivots. Therefore, this study was carried out on a 30 hm2 potato field located 650 km south of Riyadh, the capital city of the Kingdom of Saudi Arabia, to investigate the impacts of the center pivot irrigation distribution uniformity on the crop development and the spatial distribution of residual soil N. Irrigation performance test was designed to investigate water application rate and distribution uniformities. The overall water application uniformity coefficients (Cu), determined through Christiansen (Cud) and Heerman (CuH) methods, were determined at 81.29% and 80.64%, respectively. However, the overall water distribution uniformity (Du) was determined at 70%. A considerable variability in the distribution uniformity of irrigation water was observed across the experimental field (a Du value of 67% over the medium spans compared to a Du value of 88% over the inner spans). Results of this study showed a linear correlation between the irrigation water distribution uniformity and the soil N (R2=0.88). On the other hand, the vegetation cover distribution, indicated by the Cumulative Normalized Difference Vegetation Index (CNDVI), was not found to be much responsive to the irrigation distribution uniformity (R2=0.11). A time series of successive NDVI maps extracted throughout the potato crop growth stages showed a consistent trend in the distribution of NDVI across the field, with R2 values that ranged between 0.25-0.73.Keywords: irrigation performance, uniformity, center pivot, potato, soil nitrogen, NDVIDOI: 10.25165/j.ijabe.20191201.3684Citation: Al-Gaadi K A, Hassaballa A A, Tola E, Kayad A G, Madugundu R, Assiri F, et al. Impacts of center pivot irrigation system uniformity on growth of potato crop and residual soil nitrogen. Int J Agric & Biol Eng, 2019; 12(1): 126–131.